Suicide deaths and substance use in Spain between 2010 and 2022 - Flórez, Gerardo; Espandian, Ashkan; Seoane-Pillado, Teresa; Llorens, Noelia; Gerpe, José Manuel; Saiz, Pilar (Frontiers in Psychiatry, 2024)
Background: Suicide is a serious public health problem that affects our entire country. The aim of this research was to study the variation in completed suicide rates between 2010 and 2022 in Spain and their relationship with the consumption of addictive substances.Completed suicide data from the Spanish Statistical Office (INE) were analyzed with a joinpoint regression model to determine time trends. The relationship between the variation in completed suicide rates with sociodemographic variables, including depression rates, obtained from the Spanish Statistical Office and variables related to the consumption of substances obtained from the survey on alcohol and other drugs in Spain (EDADES) of the Government Delegation for the National Plan on Drugs (DGPNSD) was also studied using an exploratory analysis and also performing a Generalized Additive Model.The joinpoint regression model did reveal a point of significant change in the period studied for Spain showing a trend of increased suicide death rates for the studied period. The following variables correlated positively with the variation in completed suicide rates in the Generalized Additive Model: alcohol use in the past 12 months, alcohol use in the last 30 days, daily alcohol use in the last 30 days, binge drinking in the last 12 months, binge drinking in the last month, positive Alcohol Use Disorder Test for risky alcohol use, benzodiazepine use in the last 12 months, benzodiazepine use in the last month, daily benzodiazepine use in the last month, use of illegal substances in the last 12 months, use of illegal substances in the last month, mean age and depression rates.Applying preventive strategies on the risky consumption of alcohol, benzodiazepines and illegal substances would help reduce the rates of completed suicide in Spain.